458 Antitumor mechanisms of local radiation and combination immunotherapy in an immunologically cold model of neuroblastoma. (9th November 2020) - Aiken, Taylor; Voeller, Julie; Erbe, Amy; Rakhmilevich, Alexander; Sondel, Paul
Abstract : Background: The standard treatment for high-risk neuroblastoma includes a combination immunotherapeutic approach consisting of IL-2, GM-CSF, and monoclonal antibodies directed against GD2, a disialoganglioside preferentially expressed in neuroblastoma and melanoma (1). We recently described an effective a preclinical in-situ vaccination strategy combining local radiation therapy (RT), IL-2-linked to anti-GD2 monoclonal antibody (intratumoral immunocytokine, IT-IC), checkpoint inhibition (anti-CTLA4), and drivers of innate immunity (anti-CD40 and CpG) (2). This strategy is effective in curing mice with immunologically-cold neuroblastoma. We sought to better characterize the anti-tumor mechanisms that mediate this effect. Methods: Mice bearing GD2-expressing, immunologically-cold neuroblastoma tumors (9464D-GD2) were treated with 12Gy RT and combination immunotherapy (IT-IC, anti-CTLA-4, CpG, anti-CD40) over 12 days as previously described (2). Depletion of individual immune cell sets during treatment was achieved by depleting monoclonal antibodies and confirmed by flow cytometry. T-cell receptor deficient (TCR KO) mice were used to confirm findings in T-cell depletion experiments. 9464D-GD2 parental cells have low MHC-I expression; subclones with low and moderate MHC Class I expression were obtained by flow cytometry sorting and the impact of MHC class I expression on immune cell infiltrate and survival was assessed. Results: The effectiveness of RT and combination immunotherapy was not significantly reduced by NK or T cell depletion, and TCR KO mice had similar tumor growth and survival to mice that underwent T-cell depletion. Moderate MHC class I expression did not slow tumor growth or improve survival in mice bearing 9464D-GD2 tumors (over those with low MHC-I) following treatment. Moderate MHC class I expression also did not alter individual immune cell subsets in treated tumors. Overall, increased infiltration of CD8 T-cells, CD4 T-cells, and depletion of T regulatory cells was observed in all treated tumors (p<0.05). Conclusions: Treatment with RT and combination immunotherapy (IT-IC, anti-CTLA4, anti-CD40, CpG) may act through mechanisms that are MHC class I, NK-cell and T-cell independent. Further investigation of the role of innate immunity and myeloid subsets in this scenario is warranted. Acknowledgements: Research reported in this publication was supported by the National Cancer Institute of the National Institutes of Health under Award Number T32 CA090217. References: Yu AL, Gilman AL, Ozkaynak MF, London WB, Kreissman SG, Chen HX, et al. Anti-GD2 Antibody with GM-CSF, Interleukin-2, and Isotretinoin for Neuroblastoma. New England Journal of Medicine 2010;363:1324–34 Voeller J, Erbe AK, Slowinski J, Rasmussen K, Carlson PM, Hoefges A, et al. Combined innate and adaptive immunotherapy overcomes resistance of immunologically cold syngeneic murine neuroblastoma to checkpoint inhibition. Journal for Immunotherapy of Cancer 2019;7:13